THE APPLICATION OF MASHRABIYA (LATTICEWORK) PRINCIPLES IN MODERN TROPICAL ARCHITECTURE FOR ENERGY-EFFICIENT PASSIVE COOLING - Hanantatur Adeswastoto; Shakib Ahmed; Aylin Erdogan (Journal of Moeslim Research Technik, 2025)
The increasing reliance on energy-intensive active cooling systems in modern tropical architecture presents a significant challenge to sustainable development. Traditional, vernacular design strategies, such as the Islamic Mashrabiya (ornate latticework screens), offer time-tested principles for passive climate mitigation that are largely underexplored in contemporary building science. This study aims to quantitatively evaluate the effectiveness of integrating Mashrabiya-inspired building facades as a passive cooling strategy to reduce solar heat gain and enhance thermal comfort in modern tropical buildings. A quantitative, simulation-based methodology was employed. Using building performance simulation software (EnergyPlus), a prototypical contemporary office building in a hot-humid tropical climate was modeled. Several facade designs incorporating different Mashrabiya patterns, porosities, and materials were simulated and compared against a conventional glazed curtain wall baseline. Key performance indicators included indoor operative temperature, solar radiation transmittance, and annual cooling energy demand. The findings demonstrate that facades with optimized Mashrabiya-inspired designs significantly improved building performance. The best-performing screen designs reduced direct solar heat gain by up to 55% and lowered the annual cooling energy consumption by over 25% compared to the baseline, while still maintaining sufficient daylight levels.  The application of Mashrabiya principles is a highly effective and viable passive design strategy for modern tropical architecture. This research confirms that reinterpreting traditional architectural elements offers a culturally resonant and sustainable pathway to creating energy-efficient and comfortable buildings.